PEMANFAATAN MODEL PEMBELAJARAN E-LEARNING BERBASIS ARTIFICIAL INTELEGENT (AI) PADA PENDIDIKAN ISLAM - Rusdiana, Rusdiana; AR, M. Ramli (Program Studi PAI STAI Al Falah Banjarbaru, 2024)
Abstract: The purpose of this research is to describe the Utilization of Artificial Intelligence (AI) Based E-learning Learning Model in Islamic Education. This research describes the definition of AI-based E-learning Learning Model and the type of AI-based E-learning application or website that can be utilized in Islamic education. The research method used is literature research. The data collection technique used is reviewing, reading and writing data obtained from various sources both journals and relevant books. While the data analysis technique of this research is data reduction, data presentation and conclusion drawing. The result of this research shows that E-learning based on Artificial Intelligence (AI) is one type of learning model that utilizes the sophistication of technology integrated with Artificial Intelligence (AI). E-learning model based on Artificial Intelligence (AI) is an online learning system that utilizes AI technology to increase the effectiveness, personalization, and interactivity of the learning process. The scope of Islamic education that can utilize the sophistication of E-learning models based on Artificial Intelligence (AI) includes Al-Quran and Hadith, Akidah Akhlak, Fiqh and Islamic History. In addition, there are several kinds of applications or websites that can be useful in Islamic education namely Virtual Assistants and Chatbots Using AI Are Here to Stay | World Economic Forum, AI Chatbot, Voice Assistant, Assess.ai. Keywords: Artificial Intelligence (AI), E-learning, Islamic Education, Learning Model. Abstrak: Tujuan penelitian ini untuk mendiskripsikan Pemanfaatan Model Pembelajaran E-learning Berbasis Artificial Intelegent (AI) Pada Pendidikan Islam. Dalam penelitian ini menggambarkan seputar pengertian Model Pembelajaran E-learning Berbasis Artificial Intelegent (AI) serta jenis aplikasi atau website E-learning Berbasis Artificial Intelegent (AI) yang dapat dimanfaatkan pada pendidikan Islam. Metode penelitian yang digunakan adalah penelitian kepustakaan atau literatur. Adapun teknik pengumpulan data yang digunakan adalah menelaah, membaca serta menulis data yang didapatkan dari berbagai sumber baik jurnal maupun buku yang relevan. Sedangkan teknik analisis data penelitian ini ialah reduksi data, penyajian data dan penarikan kesimpulan. Hasil dari penelitian ini menunjukan bahwa E-learning berbasis Artificial Intelegent (AI) adalah salah satu jenis model pada pembelajaran yang memanfaatkan kecanggihan teknologi yang diintegrasikan dengan Artificial Intelegent (AI). Model pembelajaran E-learning berbasis Artificial Intelligence (AI) ialah suatu sistem pembelajaran daring yang memanfaatkan teknologi AI untuk meningkatkan efektivitas, personalisasi, dan interaktivitas proses pembelajaran. Ruang lingkup pendidikan Islam yang dapat memanfaatkan kecanggihan model pembelajaran E-learning berbasis Artificial Intelligence (AI) mencakup Al-Quran dan Hadits, Akidah Akhlak, Fiqih serta Sejarah Islam. Selain itu terdapat beberapa macam aplikasi atau website yang mampu bermanfaat pada pendidikan Islam yakni Virtual Assistants and Chatbots Using AI Are Here to Stay | World Economic Forum, Chatbot AI, Voice Asisstant, Assess.ai. Kata Kunci: Artificial Intelegent (AI), E-learning, Model Pembelajaran, Pendidikan Islam.